Darʹbarah-i ittiḥād-i nīrūʹhā dar ṣufūf-i Jabhah-i Millī-i Pidar Vaṭan-i J. D. A. - Pāyish, Nūr Akbar (Maṭbaʻah-ʻi Dawlatī, 1980)
On the need for solidarity within the ranks of Jabhah-i Millī-i Pidar Vatan; a pro-Russian organization in Afghanistan.